(3QSGdI aj YOe hLhH GdMeS aj GdMWHs - (3GdMSf Hf CMeO GdLdGds ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje SCd GdhdO MeGg Gddg Yf hLg JMejS GdMWH ai GdLgI GdReGfjI adjYde Ydeg Gddg Cf gPG GdeSFhd Yfg ai eSGFd GdaQhY hGf efGWgG GdELJgGO s
(3BNQgG (B:s
(3hJMQje eGd GdeSdejf bWYi eYdhe ef VQhQI GdOjf hEcQGg Cgdg Ydjg efGma ddhQY HGdcdjI hTGgO Ydi aGYdg HGdWeY ai GdOfjG GdOfjI YUefG Gddg Yf GdTQc hhabfG dUGdM GdYed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eLGejY s
Keywords: (3GdeLGejYs